PENGARUH KAPASITAS DAN PEMBERDAYAAN TERHADAP KESEJAHTERAAN PERAJIN INDUSTRI KERAJINAN SANGGAH DI KECAMATAN MENGWI KABUPATEN BADUNG - Arya Suistyan, I Wayan Purdana; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
The development of handicraft industry in Bali Province has the potential to be developed, given the local natural resources and the creativity of the community in the field of arts or crafts enough to contribute to improving the welfare of the community. The purpose of this study is to analyze the capacity and empowerment of artisans sanggah crafters industry in the District Mengwi Badung regency either simultaneously or partially. For this purpose multiple linear regression analysis and factor analysis were used. The results of data analysis show simultaneously capacity and empowerment, affecting the prosperity of artisans sanggah craft industry in Mengwi Sub-district Badung. Partially, the capacity and empowerment of crafters have a positive and significant impact on the prosperity of crafters of sanggah craft industry in Mengwi Sub-district of Badung Regency. Keywords: Capacity, Empowerment, Welfare .